Fatal hyalohyphomycosis with cutaneous involvement caused by Purpureocillium lilacinum in an immunocompromised patient with bullous pemphigoid. - Corbeddu, Marialuisa; Ferreli, Caterina; Cappai, Riccardo; Ferraguti, Patrizia; Atzori, Laura; Pilloni, Luca; Rongioletti, Franco (Acta Biomedica Atenei Parmensis, 2021)
Emergent pathogen as Purpureocillium lilacinum are becoming cause of morbidity and mortality in our population, especially in immunocompromised patients. We describe a case of hyalohyphomycosis in a diabetic man under systemic steroid treatment for a bullous pemphigoid. Treatment with different antimycotic drugs were ineffective and infection spread diffusely, leading to deterioration of general conditions and ultimately death. The aim of this article is to increase awareness of clinicians about this uncommon, but frequently fatal refractory mycotic infection.